Pengaruh Rasio Keuangan dan Kondisi Financial Distress Terhadap Struktur Modal Pada Perusahaan Manufaktur Goldenblossom Sumatera (Gbs) - Dani Masardi; Maulan Irwadi; Lukita Tripermata (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
This study aims to examine the effect of financial ratios and financial distress on the capital structure of the manufacturing company Golden Blossom Sumatra (GBS). This research uses secondary data. In the data collection stage, researchers used documentation techniques. The collected data were then analyzed using multiple linear regression methods. The results of this study indicate that the activity ratio and profitability ratio have a positive effect on the capital structure, while the liquidity ratio, solvency and financial distress have no positive effect on the capital structure.